2016
DOI: 10.1016/j.mimet.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Microbial signatures of oral dysbiosis, periodontitis and edentulism revealed by Gene Meter methodology

Abstract: Conceptual models suggest that certain microorganisms (e.g., the "red" complex) are indicative of a specific disease state (e.g., periodontitis); however, recent studies have questioned the validity of these models. Here, the abundances of 500+ microbial species were determined in 16 patients with clinical signs of one of the following oral conditions: periodontitis, established caries, edentulism, and oral health. Our goal was to determine if the abundances of certain microorganisms reflect dysbiosis or a spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Contrariwise, periodontitis, as a biofilm disease (Schaudinn et al, 2009 ), may result from the integration of various causative parameters. Bacteria are among these parameters and the composition of the microbial communities accurately correlates with clinical outcome (Feres et al, 2016 ; Hunter et al, 2016 ). Indeed, some species can be efficiently used as markers for diagnosis (Meuric et al, 2017 ), re-opening ways for considerations about the use of bacterial identification–though in a multi-variate fashion–for epidemiology or treatment follow-up.…”
Section: Microbiology Of Periodontitis: the Bacterial Paradigmmentioning
confidence: 99%
“…Contrariwise, periodontitis, as a biofilm disease (Schaudinn et al, 2009 ), may result from the integration of various causative parameters. Bacteria are among these parameters and the composition of the microbial communities accurately correlates with clinical outcome (Feres et al, 2016 ; Hunter et al, 2016 ). Indeed, some species can be efficiently used as markers for diagnosis (Meuric et al, 2017 ), re-opening ways for considerations about the use of bacterial identification–though in a multi-variate fashion–for epidemiology or treatment follow-up.…”
Section: Microbiology Of Periodontitis: the Bacterial Paradigmmentioning
confidence: 99%
“…They were especially effective in reducing S. gordonii and T. denticola in the biofilm. S. gordonii along with 16 other genera, has been previously classified under ‘signatures of dysbiosis’ due to its predominance in patients with periodontitis and edentulism (Hunter et al , 2016). Also, its role in co-aggregation and metabolic interactions with other periodontal pathogens is well-known (Hajishengallis and Lamont, 2016; Sakanaka et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized to be associated with human infections [ 26 , 36 , 45 47 ], and are able to survive within oral epithelial cells as well as to modulate the epithelial immune response, leading to initiation and progression of periodontal diseases [ 25 ]. Bacteria of the Thiobacillus genus that belong to the SOB group were only sometimes detected in the human oral cavity [ 21 , 48 , 49 ]. However, it already has been shown that many bacterial genera have been identified by DNA sequencing, but they were not detected using the microarray probes which did not target the 16S rRNA genes specific for the bacteria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria of the Thiobacillus genus that belong to the SOB group were only sometimes detected in the human oral cavity [ 21 , 48 , 49 ]. However, it already has been shown that many bacterial genera have been identified by DNA sequencing, but they were not detected using the microarray probes which did not target the 16S rRNA genes specific for the bacteria [ 49 ].…”
Section: Discussionmentioning
confidence: 99%